PENGARUH SURFAKTAN PEG-7 GLYCERYL COCOATE-SPAN80 DAN PEG-40 HYDROGENATED CASTOR OIL-SPAN80 TERHADAP KARAKTERISTIK FISIK KRIM alfa-ARBUTIN - Yuli Ainun Najih; Yuyun Nailufa; Dita Nurlita Rakhma; Nur Hardianti Ruchmana (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
?-arbutin is a derivative of hydroquinone to treat hyperpigmentation disorders which acts as a tyrosinase inhibitor. The hydrophilic nature of ?-arbutin requires a dosage form that can increase its penetration into the skin is a cream. The purpose of this study was to determine the effect of surfactants PEG-7 Glyceryl Cocoate-Span80 and PEG-40 Hydrogenated Castor Oil-Span80 on the physical characteristics of ?-arbutin cream. The cream formulation made into 2 formula, F1 using PEG-40 Hydrogenated Castor Oil-Span80 and F2 using PEG-7 Glyceryl Cocoate-Span80. Physical characteristics including organoleptic testing, emulsion type, pH, viscosity and Spreadability. The results obtained from the two cream formulas showed a significant difference in the measurement of pH, viscosity and Spreadability values. The results of the pH value of F1 and F2 are 5.74 and 6.24. The viscosity results obtained from F1 and F2 are 50500cPs and 43333cPs. The spreadability measurement results obtained from F1 and F2 were 9.93cm and 11.33cm. The results spreadability will be inversely proportional to the results of the viscosity obtained. The higher the viscosity yield, the smaller the spreadability of a cream.